GROWTH PERFORMANCE AND ECONOMIC ANALYSIS OF REPLACING SOYA BEAN MEAL WITH TOASTED SORREL SEED MEAL IN THE DIETS OF WEANER RABBITS - Igila, T. T.; Doma, U. D.; Muhammad, A. S.; Sani, I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to evaluate the growth performance and economic analysis of replacing soybean meal with toasted sorrel seed meal (TSSM) in the diets of weaner rabbits. The experiment was carried out at the Rabbitry Unit of the Department of Animal Production, Abubakar Tafawa Balewa University, Bauchi, Nigeria. A total of forty (40) weaner rabbits were used in a Completely Randomized Design consisting of five dietary treatments (T1–T5) with four replicates per treatment and two rabbits per replicate. The diets contained TSSM at inclusion levels of 0, 25, 50, 75 and 100%, replacing soybean meal. The feeding trial lasted for six (6) weeks. Sorrel seeds (Hibiscus sabdariffa L.) were obtained locally, cleaned, toasted, milled into meal and incorporated into the experimental diets. Data collected included feed intake, body weight gain, feed conversion ratio (FCR) and economic indicators such as total feed cost, feed cost per kilogram gain and cost savings. Results showed that, final body weight increased significantly (p < 0.05) from 1,550.50 g in diet 1 to 1,795.60 g in diet 4, while daily weight gain also improved from 11.05 g in diet 1 to 14.90 g in diet 5. Feed intake remained stable across all treatments. Feed conversion ratio (FCR) improved from 5.79 (T1) to 4.30 (T5), while feed efficiency increased from 0.17 to 0.23. Economic analysis revealed that feed cost per kilogram decreased steadily from ₦290.55 (T1) to ₦205.01 (T5) and feed cost per kilogram weight gain reduced from ₦781.58 in the control to ₦463.86 in the 100% inclusion group. Correspondingly, cost savings increased from ₦0.00 in T1 to ₦317.72 in T5, indicating strong economic benefits. It was concluded that, toasted sorrel seed meal can effectively replace soybean meal up to 100% in the diets of weaner rabbits without adverse effects on their growth while significantly reducing feeding costs and improving profitability. It is therefore recommended that TSSM be included up to 100% in weaner rabbit diets to enhance growth performance and economic returns.